ANALISIS NILAI TAMBAH DAN PEMASARAN PRODUK UMKM BANDENG PRESTO SHANUM 86 KIARACONDONG, BANDUNG - Junianto, Junianto; Puspita, Meyla; Arnessa, Hilda; Syah, Alliya; Bazri, Muhammad (Institute of Computer Science (IOCS), 2025)
Micro, Small and Medium Enterprises (MSMEs) play an important role in increasing the added value of products and absorbing labor. One of the MSMEs engaged in milkfish processing in Bandung is Bandeng Presto Shanum 86, which has been operating since 2022 and utilizes various digital platforms in its marketing. This study aims to analyze the added value and marketing characteristics of the Shanum 86 Presto Milkfish product. The method used in the study is the survey method. The research parameters are the analysis of the added value of milkfish processed into presto milkfish. Other parameters are the marketing characteristics of presto milkfish products which include marketing design, product design, price design, promotion design, distribution/location design, and consumer analysis. Data were obtained by interviewing presto milkfish business owners. Data related to added value were analyzed using the Hayami method. Data related to marketing characteristics were analyzed descriptively. The results of the study showed that the added value ratio of milkfish processed into presto milkfish carried out by UMKM Presto Shanum 86 was 23.46%, categorized as moderate. The target consumers are the middle to upper market, especially families, traditional culinary lovers, resellers, as well as employees, and students. Marketing challenges include limited access for consumers who rely on physical stores, but opportunities are open with the expansion of the reseller network and increased digital marketing. The competitive advantage of Shanum 86 Presto Milkfish lies in its soft bones, distinctive taste, and shrimp paste chili sauce. Marketing design focuses on product design, price, promotion, and distribution.